2011
DOI: 10.1007/s11262-011-0622-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative complete genome analysis of Indian type A foot-and-mouth disease virus field isolates

Abstract: Comparative complete genome analysis of 17 serotype A Indian field isolates representing different genotypes and sub-lineages is presented in this report. Overall 79% of amino acids were invariant in the coding region. Chunk deletion of nucleotide was observed in S and L fragment of 5'-UTR. More variability which is comparable to that of capsid coding region was found in L and 3A region. Functional motifs and residues critical for virus biology were conserved most. Polyprotein cleavage sites accepted few chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…However, previous comparative genomic studies of FMDV [7] have highlighted two instances of similar deletions for serotype A isolates from Argentina in 1959 and 1961 (AY593769 and AY593789) and one additional serotype C isolate from the UK in 1934 (AY593810). Likewise, a 41 nt deletion within the same region was found for serotype A viruses from India in 2009 (HQ832592) [34]. The results obtained in the present study using maximum likelihood analysis of the S-fragment and the VP1-coding region of isolates with and without deletions indicate that this deletion has arisen independently in these different serotypes and have not been transferred via recombination from a single event generated in one common ancestor.…”
Section: Discussionsupporting
confidence: 69%
“…However, previous comparative genomic studies of FMDV [7] have highlighted two instances of similar deletions for serotype A isolates from Argentina in 1959 and 1961 (AY593769 and AY593789) and one additional serotype C isolate from the UK in 1934 (AY593810). Likewise, a 41 nt deletion within the same region was found for serotype A viruses from India in 2009 (HQ832592) [34]. The results obtained in the present study using maximum likelihood analysis of the S-fragment and the VP1-coding region of isolates with and without deletions indicate that this deletion has arisen independently in these different serotypes and have not been transferred via recombination from a single event generated in one common ancestor.…”
Section: Discussionsupporting
confidence: 69%
“…FMDV serotype A topotype Asia, genotype 18 has been the only genotype present in India since 2001. This genotype is further classified into the VP3 59 ‐deletion and non‐deletion groups (Mohapatra et al., ; Subramaniam et al, ). Genotype 18 has also been found in Bangladesh in recent years (Mohapatra et al., ; Nandi et al., ; WRLFMD, ).…”
Section: Endemic Pools In Asiamentioning
confidence: 99%
“…In fact, Valdazo-González et al (2013) described an FMDV isolate with a 70-nt deletion in the S fragment located at positions 148–217 of O/HKN/15/2010. Serotype A isolates found in Argentina in 1959 and 1961 ( Carrillo et al, 2005 ), serotype C isolate from the United Kingdom ( Carrillo et al, 2005 ), and serotype A viruses from India found in 2009 ( Subramaniam et al, 2011 ), all have deletions in the S fragment upper-loop, yet they remain infectious. This evidence strongly suggests that the S fragment of the 5′-UTR can tolerate some deletions without compromising pathogenicity.…”
Section: ′- and 3′-viral Utr Rnas Influence The Course Of Infectionmentioning
confidence: 99%